A 10. századi besenyő törzsszervezet és szállásterület problémáinak újragondolása - Kovács Attila (Belvedere Meridionale, 2011)
Munkámban a besenyők szállásterületének méretével, kiterjedésével, azon belül a törzsek elhelyezkedésének kérdésével foglalkozom, és az abból levonható következtetések összefoglaló rendszerezésére teszek kísérletet. A kérdéskör magában foglalja a besenyők politikai rendszerének értelmezését is. A besenyők európai honfoglalásának, majd megtelepedésének kérdéskörét sokan taglalták és számos elmélet született a témában, amelyek rendszerint kitértek a besenyő törzsek közötti hierarchia problematikájára is. Ezen felül részletesen vizsgálták a besenyő törzsek elnevezéseit, és többen kísérletet tettek a nomád besenyők katonai és politikai struktúrájának rekonstruálására. The power structure and location of Pechenegs in the 10th century was badly re-enacted based on earlier historical works. The correction is possible only by the thorough use of sources and by in taking other points of view. The theme has to be examined in its complexity. The present-day Byzantine source starts the exposition of Pechenegs with the description of eastern tribes not with the western ones. From this a number of persons made that bad conclusion that the western tribes of Pechenegs were the chief tribes. The leading role of Kangars among the Pecheneg tribes was also a misunderstanding. It is similar to the status of Kabar tribes among Hungarian tribes. At nomadic folks the aristocratic valiant denomination and those lead the way in the battles are not the signs of leading role but the signs of the subjugated role as a military aid folk. The basis of nomadic farming is the animal stock. The bigger grassland (steppe) they had the more animal they could keep so that they counted richer. The home of the Pechenegs is the area between the down-Danube and the Don. The grassland on the east side of Dnieper is two and a half times bigger than the one on the west side. The commerce also important was to the nomads. On the east side of the Dnieper were all the important commerce routes. It is also significant that at the nomad’s the leading tribe or tribe group gave the name of the whole association of tribes. If the Kangars would have lead the association of tribes then they wouldn’t be endured in the sources as Besenyő but as Kangar association of tribes. From the work of the Byzantine Emperor a special nomadic political system is tracing out. The solution is that the Szurukülbej was the leading tribe and the eastern tribes were the dominant ones while the Kangars were in subjugated status. The berth of the eight tribes can be easily described by the comparison of the hierarchic and the regional lists of the source.